Effect of A1 doping on the microstructure and electrical transport properties of YBCO superconductor - Muhammad Irfan, Izham (2016)
Superconductor used is YBa2Cu307 (YBCO) with addition dopant element of Aluminium (AI). The AI203 doping is used to study the microstructure and electrical transport properties of YBCO superconductor. Process involved in preparation of YBCO superconductor is by using solid state reaction method. The superconductors were prepared with different composition of aluminium oxide doping which are 0.01 wt%, 0.02 wt%, 0.03 wt%, 0.04 wt%. The samples were tested with four analyses which are for phase formation; X-Ray Diffractometer (XRD) is used, for microstructure; Scanning Electron Microscopy (SEM) is used, for critical current; Four Point Probe is used, and for Meissner Effect of superconductors. The results obtained for XRD can be conclude that YBCO compound having an orthorhombic structure which shows superconducting behaviour. For SEM results, the microstructure obtain is almost the same with constant or pure YBCO superconductor although doping process were done to the samples this is due to the concentration of magnetic nanoparticles were too small to act as impurity and to cause porous structure. Next, for four point probe testing, the result obtained is the resistance value = 0 Ω when cooled at critical temperature, Tc but some errors might occur that causes some changes to the results. Lastly, Meissner Effect test shows that the critical temperature of YBCO superconductor is high when addition of AI203 element is added, compared to pure YBCO superconductor.